Post-Keynesian Institutionalism after the Great Recession - Charles J. Whalen (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2013)
This article surveys the context and contours of contemporary Post-Keynesian Institutionalism (PKI). It begins by reviewing recent criticism of conventional economics by prominent economists as well as examining, against the backdrop of the current context, important research that paved the way for PKI today. Then it sketches essential elements of PKI – drawing heavily on the contributions of Hyman Minsky – and identifies directions for future research. Although there is much room for further development, PKI offers a promising starting point for economics after the Great Recession.
Keywords: B25; B52; E12; E32; 330; Post-Keynesian Institutionalism; institutional economics; post-Keynesian economics; financial instability; money manager capitalism; Hyman Minsky